2017
DOI: 10.1021/acs.estlett.7b00341
|View full text |Cite
|
Sign up to set email alerts
|

High N2O5 Concentrations Observed in Urban Beijing: Implications of a Large Nitrate Formation Pathway

Abstract: The heterogeneous hydrolysis of dinitrogen pentoxide (N2O5) is important to understanding the formation of particulate nitrate (pNO3 –). Measurements of N2O5 in the surface layer taken at an urban site in Beijing are presented here. N2O5 was observed with large day-to-day variability. High N2O5 concentrations were determined during pollution episodes with the co-presence of large aerosol loads. The maximum value was 1.3 ppbv (5 s average), associated with an air mass characterized by a high level of O3. N2O5 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
133
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(176 citation statements)
references
References 38 publications
(61 reference statements)
19
133
2
1
Order By: Relevance
“…(3) and (5), high S a , high NO x , low k NO 3 , or low temperature allow the N 2 O 5 uptake to more easily be located in the γ N 2 O 5 -insensitive region. Here, the critical value of the N 2 O 5 uptake coefficient (2 × 10 −3 ) was relatively low com- pared with that recommended for the surface of mineral dust (0.013, 290-300 K; Crowley et al, 2010b;Tang et al, 2017) or determined in many field experiments (e.g., S. S. Brown et al, 2006bBrown et al, , 2009Wagner et al, 2013;Morgan et al, 2015;Phillips et al, 2016;Brown et al, 2016;Wang et al, 2017b;. This suggests that the NO x loss and pNO − 3 formation by N 2 O 5 uptake were easily maximized in the pollution episode and further worsened the PM pollution.…”
Section: Sensitivity Studiesmentioning
confidence: 63%
See 1 more Smart Citation
“…(3) and (5), high S a , high NO x , low k NO 3 , or low temperature allow the N 2 O 5 uptake to more easily be located in the γ N 2 O 5 -insensitive region. Here, the critical value of the N 2 O 5 uptake coefficient (2 × 10 −3 ) was relatively low com- pared with that recommended for the surface of mineral dust (0.013, 290-300 K; Crowley et al, 2010b;Tang et al, 2017) or determined in many field experiments (e.g., S. S. Brown et al, 2006bBrown et al, , 2009Wagner et al, 2013;Morgan et al, 2015;Phillips et al, 2016;Brown et al, 2016;Wang et al, 2017b;. This suggests that the NO x loss and pNO − 3 formation by N 2 O 5 uptake were easily maximized in the pollution episode and further worsened the PM pollution.…”
Section: Sensitivity Studiesmentioning
confidence: 63%
“…Particulate nitrate formation via N 2 O 5 heterogeneous hydrolysis in summer was proved efficient by ground-based observation in North China (Wang et al, 2017b; and found comparable to or even higher than the daytime formation. Several studies showed that N 2 O 5 hydrolysis is responsible for nocturnal pNO − 3 enhancement in summer in Beijing (Pathak et al, 2009(Pathak et al, , 2011Wang et al, 2017a).…”
Section: Introductionmentioning
confidence: 83%
“…S1), likely suggesting the effects of SO 2 emission control over China in the recent years (Sun et al, 2015b). Previous studies also showed nitrates dominating the secondary inorganic species of aerosols (Sun et al, 2015b;Zheng et al, 2015;Wang et al, 2017 (Fig. S1), which made these elements difficult to emit into the air (Tian et al, 2014).…”
Section: Chemical Properties Of Aerosols At Different Pollution Levelsmentioning
confidence: 77%
“…HO 2 and RO 2 concentrations were detected as OH after chemical conversion by adding excess NO in another two separated cells. Detailed information of this instrument can be found in the paper by Tan et al (2017) and the references therein. Only a brief description of the radical 20 instrument is presented here.…”
Section: Oh Ho 2 and Ro 2 Measurementsmentioning
confidence: 99%
“…Also for this environment, there is a tendency of underestimating OH for conditions when NO was less than 300 pptv. Additionally, a missing peroxy radical source was found for the high NO x regime showing a severe underestimation of local ozone production (Tan et al, 2017).…”
mentioning
confidence: 96%